A Mathematical Model for the Alkylation of o-Cresol with Cyclohexanol - Ashaduzzaman, M; Saha, Manoranjan; Islam, Shams Tania Afroza; Ismail, Mohammad; Sharif, Nashid; Galib, Mirza (Bangladesh Journal of Scientific and Industrial Research, 2009)
A mathematical model was developed for the alkylation of o-cresol with cyclohexanol in the presence of perchloric acid as a catalyst. A set of trials was planned according to a 3 factor 2-level Yates pattern experimental design. The variables chosen for the study were temperature, molar ratio of o-cresol to cyclohexanol and amount of perchloric acid. The critical response was the yield of cyclohexyl o-cresol. Main effects as well as two-and three-factor interaction effects were statistically significant. The adequacy of the suggested model was checked up. The highest experimentally found yield was 89.3% while the estimated yield was found to be 89.09%. The experimentally settings were temperature, 140O C; molar ratio of o-cresol to cyclohexanol, 6:1; amount of catalyst, 5% by wt. of o-cresol; addition time, 2 h; stirring time, 1 h. Keywords: o-Cresol, Cyclohexanol, Experimental design, Alkylation. DOI: 10.3329/bjsir.v44i2.3669 Bangladesh J. Sci. Ind. Res. 44(2), 181-186, 2009